A Systematic Clinical Framework for Postimplantation Monitoring in Thalamic Neuromodulation: Insights From Twiddler's Syndrome - Shalin Shah; Ganne Chaitanya; Jeston Chin; Nicholas Delcimmuto; Jay R. Gavvala (Annals of Clinical and Translational Neurology)
ABSTRACT This case described a 25‐year‐old pregnant woman with refractory multifocal epilepsy, diagnosed in 2020 and treated with bilateral thalamic deep brain stimulation (DBS) targeting the centromedian and pulvinar nuclei. Prior to DBS, she experienced daily focal seizures, often progressing to generalized tonic–clonic seizures despite optimal medication. Presurgical evaluations revealed multifocal epilepsy with right hemispheric involvement and diffuse band heterotopia. Given the extensive neurophysiological and radiographic findings, DBS was chosen over resective surgery. Following implantation in December 2023, initial stimulation settings resulted in some seizure control but also development of new symptoms, including shock‐like sensations down her neck. After 43 seizure‐free days, she experienced a prolonged seizure in April 2024, prompting further investigation. Imaging revealed migration of the right pulvinar electrode, which was identified as the likely cause. This resultant displacement, called the “Twiddler's Syndrome,” is a phenomenon where device manipulation causes malfunction or dislodgment. This resulted from the patient's habit of massaging her neck. After adjusting DBS settings and turning off right pulvinar stimulation, her symptoms resolved, and she remained seizure‐free for two months. This case emphasizes the need for careful postimplantation monitoring, imaging, and awareness of hardware‐related issues like Twiddler's Syndrome, highlighting the importance of well‐planned surgical strategies to optimize outcomes in neuromodulation therapies.